Two-Stage Repair of Aortic Arch Hypoplasia Associated with Other Congenital Heart Defects in Newborns and Infants - Y. Truba; I. Dziuryi; R. Sekelyk; O. Golovenko; V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2021)
Background. The optimal tactics of surgical treatment of aortic arch hypoplasia combined with other congenital heart defects remain controversial. In recent years, the leading clinics of the world prefer one-stage repair of such a combination, however, two-stage treatment is still used by cardiac surgeons and remains one of the variants of surgical tactics.The aim. To analyze immediate and long-term results of a two-stage repair of aortic arch hypoplasia with other con-genital heart defects in newborns and infants.Materials and methods. The study included 138 infants who were selected for a two-stage repair of aortic arch hy-poplasia with other congenital heart defects. There were 79 (57.2%) male and 59 (42.8%) female patients. The mean age of the patients was 1.4 ± 0.7 months, mean body weight was 4.1 ± 2.0 kg. The main method of the defect diagnosis and evaluation of immediate and long-term results was echocardiographic examination. The aortic arch segment was consid-ered hypoplastic if the Z-score deviation was less than –2.0.Results. The hospital mortality rate was 5.8% (n = 8). Two patients (1.4%) had delayed sternal closure in the early postoperative period. As a result of severe myocardial failure, two patients underwent extracorporeal membrane oxy-genation (ECMO). According to echocardiography before discharge, the mean pressure gradient at the site of aortic arch repair was 16 ± 6 mmHg. There was one death in the follow-up period. In 16 (11.5%) patients, aortic arch restenosis developed in the postoperative period. In total, 20 re-interventions were performed: 11 endovascular balloon dilatations and 9 surgical re-interventions. In the early postoperative period, aortopexia was performed in two patients (1.4%) due to compression of the left main bronchus.Conclusions. Two-stage repair of aortic arch hypoplasia with other congenital heart defects in newborns and infants is effective and safe treatment with good immediate and long-term results. This study shows that this surgical strategy can be effectively used in this complex pathology.